Postpartum depression: A role for psychedelics?. (August 2022) - Jairaj, Chaitra; Rucker, James J
Background: Postpartum depression (PPD) is a major public health concern and has, at its core, a sense of maternal 'disconnection' – from the self, the infant, and the support system. While PPD bears similarities with MDD, there is increasing evidence for its distinct nature, especially with the unique aspect of the mother-infant relationship. Current treatment modalities for PPD, largely based on those used in major depressive disorder (MDD), have low remission rates with emerging evidence for treatment resistance. It is, therefore, necessary to explore alternative avenues of treatment for PPD. Objective: In this narrative review, we outline the potential therapeutic rationale for serotonergic psychedelics in the treatment of PPD, and highlight safety and pragmatic considerations for the use of psychedelics in the postpartum period. Methods: We examined the available evidence for the treatment of PPD and the evidence for psychedelics in the treatment of MDD. We explored safety considerations in the use of psychedelics in the postpartum period. Results: There is increasing evidence for safety, and encouraging signals for efficacy, of psilocybin in the treatment of MDD. Psilocybin has been shown to catalyse a sense of 'reconnection' in participants with MDD. This effect in PPD, by fostering a sense of 'reconnection' for the mother, may allow for improved mood and maternal sensitivity towards the infant, which can positively impact maternal role gratification and the mother-infant relationship. Conclusion: Psychedelic assisted therapy in PPD may have a positive effect on the mother-infant dyad and warrants further examination.